The geology and metallogeny of the Otavi mountain land, Damara orogen, SWA/Namibia, with particular reference to the Berg Aukas Zn-Pb-V deposit a model of ore genesis - Misiewicz, Julian Edward (Rhodes University, Faculty of Science, Department of Geology, 1988)
The Olavi Mountain Land is a 10 000 km2 mineral province located at the eastern extremity of the exposed Northern Platform of the Damara Pan African orogenic belt. The Olavi Mountain Land is tbe most important mineral province on the Northern Platform. Exploitation of tbe Cu-Pb-Zn-V province has been on-going since the possession of the territory by the German colonial authority in 1890. Production has been mostly from four mines which in order of importance are Tsumeb, Kombat, Berg Aukas and Abeoab. A second mineral province on the Northern Platform located in the west is centred on Sesfontein where as yet only insignificant mineralization has been noted. Besides these localities, the Northern Platform is conspicuously devoid of notable mineralization. The aim of this thesis has been to document tbe Berg Aukas deposit, an important end-member type of mineralization in the Otavi Mountain Land. The basic premise bas been to show tbat the derivation and localization of the mineralization is a consequence of two broad controls which can be simply summarised as features of the basement and of the carbonate sequences. The geodynamic evolution of the Damara Belt commenced with intra-continental rifting approximately 900 Ma ago. Rift grabens trending north-east were filled by the Nosib Group which comprises mostly clastic lithologies but also some volcanics. The earliest and largest rift is referred to as the Northern Rift. Separation of the Congo, Kalahari, and proto-South American cratons resulted in rifting and rapid downwarping so that an encroaching sea and an Olavi Group carbonate shelf developed along the northern margin of the Northern Rift. Significantly, the carbonates only covered the Northern Rift in the area of the Otavi Mountain Land where a basinal dome, referred to as the Grootfontein Basement High, marked the basin edge. In the west, the carbonates covered the less important Sesfonfein Rift, and it is only in these two areas where Nosib sequences underlie the carbonate platform. Carbonate sedimentation was interrupted by a major period of crustal readjustment and the deposition of an extensive mixtite throughout the geosynclinal Swakop Trough and Northern Platform. This is referred to as the Chuos Formation and subdivides the Olavi Group into a lower Abenab and an upper Tsumeb Subgroup. Reversal of spreading led to plate collision and subduction of tbe Kalahari craton beneath the Congo craton. It was accompanied by orogenesis which resulted in F1 folding of the Northern Platform into a series of north-easterly trending intermontane basins into which a molasse sequence known as the Mulden Group was unconformably deposited. Following this major north-south deformation mild east-west compression initiated F2 folding and the formation of doubly plunging synclines. The Berg Aukas Syncline represents a primary depositional basin which was subsequently folded. The original basin was formed by late Nosib rifting wben spreading caused the Swakop geosynclinal Trough to form. Carbonates of the basal Berg Aukas Formation were deposited in a lagoonal setting typified by reef and fore-reef facies witb peri-platform conditions. Rapid subsidence caused these sediments to be overlain by deep water carbonates of the Gauss Formation. Two styles of mineralization known as the Tsumeb-type and Berg Aukas-type are stratigraphically, isotopically, and mineralogically distinct. The Tsumeb-type is a cupriferous variety of discordant bodies confined to the upper sequences beneath the Mulden unconformity. The Berg Aukas-type is a Zn-Pb variety confined to tbe basal unconformity. The Berg Aukas deposit comprises three ore bodies known as the Northern Ore Horizon, the Central Ore Body, and the Hanging Wall Ore Body. Sphalerite and galena constitute the bypogene ore. Willemite, smithsonite, cerussite, and descloizite are important supergene ores. A review of genetic models concludes that a magmatic origin initially proposed for tbe Tsumeb deposit is entirely rejected and a basin dewatering model in line with Mississippi Valley-type deposits is proposed. The syntectonic nature of mineralization at Berg Aukas and elsewhere in the Otavi Mountain Land indicates that orogenesis encouraged dewatering and leaching of metals from a broad mineralizing front along the margin of the Swakop Trough. These were transported by acidic saline brines which migrated along the clastic aquifers and structural conduits provided by the Northern Rift. Fluid inclusion studies indicate that the hydrothermal fluids at Berg Aukas were very saline (23% TDS) and were transported at temperatures ranging between 92Â° to 210Â°C. Hydrothermal fluids which mineralized Berg AukaS-type deposits migrated along the basal unconformity towards the basement high and were responsible for hydrothermally altering the basement granites and gabbros and the Nosib clastic rocks. Tsumeb-type deposits resulted by migration of fluids through the carbonate pile and along north-easterly trending basement geofractures. As a consequence of variation in transport, the Berg Aukas-type and Tsumeb-type fluids leached different sources and therefore derived mineralogically and isotopically seperable characteristics. The localization of the Berg Aukas ores was controlled by the carbonate stratigraphy and structure. Hydrothermal karsting and ore deposition took place on the contact between Massive Grey and Light Grey Dolostones which represents a permeability contrast. The movement of the hydrothermal fluids was controlled by north-south trending vertical fractures caused by F2 folding which resulted in a peric1inal structure. Hydrothermal karsting was accompanied by ca1citic, dolomitic and silicic alteration. The heated acidic fluids initiated solution collapse and a variety of breccia types. Supergene processes resulted in oxidation and upgrading of the ore. Vanadium derived indirectly from gabbros in the basement complex were transported as calcium metavanadate complexes and deposited on contact with the oxidizing base metal sulphides.
Keywords: Geology -- Namibia -- Damaraland; Ore deposits -- Namibia; Orogeny; Metallogeny; Geodynamics